No evidence for collateral effects of electromagnetic fields used to increase dissolved oxygen levels on the behavior and physiology of freshwater fishes. (9th June 2022) - Elvidge, Chris K.; Bihun, Christian J.; Davis, Colin; Ulhaq, Saad; Fung, David T.; Vermaire, Jesse C.; Cooke, Steven J.
Abstract: Hypoxia in surface waters driven by warming climate and other anthropogenic stressors is a major conservation concern, and technological solutions for water quality remediation are sorely needed. One potential solution involves the use of low‐intensity electromagnetic fields (EMFs) to increase dissolved oxygen levels, but potential collateral effects of the EMFs on aquatic animals have not been formally evaluated. We examined the effects of EMF exposure on wild‐caught, captive sunfish ( Lepomis spp.) over 8‐day and 3‐day exposures, with and without aeration in mesocosms and stock tanks (respectively). We also quantified ambient fish abundance in close proximity to EMF devices deployed in Opinicon Lake (ON). We found no significant differences in a suite of blood‐based stress physiology biomarkers, behaviors, and putative aerobic capacities between EMF and control conditions over 8 days. Aerated mesocosms equipped with activated EMFs consistently had higher oxygen levels in the water than aerated controls. There were no differences in mortality during 3‐day oxygen depletion trials under EMF or control conditions, and we detected no differences in fish abundance when the devices were activated in the lake. Our findings suggest that deploying EMF devices in field settings is not likely to exert negative effects on exposed fish populations. Practitioner Points: Low‐cost, low‐energy technological solutions to remediate aquatic hypoxia are sorely needed Electromagnetic fields (EMFs) can increase oxygen flux across air/water interfaces and increase dissolved oxygen levels We found no evidence of negative effects of EMFs on fish physiology or behavior and our results support their use in alleviating hypoxic conditions Abstract : Low‐intensity EMFs can increase dissolved oxygen content of water through increased flux across the air‐water interface in the presence of mechanical agitation and have demonstrated promise to alleviate hypoxia (left) and restore natural conditions (right). This study found no evidence of any negative collateral effects of EMF exposure on the behaviour and physiology of centrarchid fishes.